Presuppositions Contain Code-Mixing in the Jeda Nulis Podcast and Their Implications in Expository Text Learning - Abdullah Muntadhir; Nur Fajar Arief (EDUTEC : Journal of Education And Technology, 2023)
The Jeda Nulis podcast has become one of the channels that offers a lot of engaging discussions and interesting content related to current issues. The objectives of this research are to describe the types of presupposition containing code-switching in the Jeda Nulis podcast, explain the factors causing code-switching in presuppositions within the Jeda Nulis podcast, and discuss the implications of the Jeda Nulis podcast in teaching expository texts to high school students (Class X). This study utilizes a qualitative approach, and the data sources are the host Habib Ja’far and guest speaker Onad. The data were obtained from language activities in a video podcast that was aired on YouTube on December 31, 2021. The research data consist of presuppositional discourse containing code-switching and the factors causing code-switching in presuppositions. Data collection techniques include documentation, observation, and note-taking. The analysis of the data reveals various types of presuppositions containing code-switching, such as existential presupposition, factual presupposition, nonfactual presupposition, lexical presupposition, structural presupposition, and counterfactual presupposition. The factors causing code-switching in presuppositions include limitations in code use, the use of more popular terms, the speaker's characteristics, the desire for prestige, the main topic of discussion, language variety and register, the interlocutor, and the use of humor.